Modern methods of monitoring and evaluating the current functional state of athletes in various types of martial arts - Revenko, V.; Puhach, Y.; Druz, V.; Artemiev, V. (Slobozhanskyi herald of science and sport, 2019)
Purpose: development of a contactless real-time monitoring system of the athlete`s current functional state.